Turbulence and productivity; an analysis of 40 Dutch regions in the period 1988-1996 - Niels Bosma; Henry Nieuwenhuijsen (European Regional Science Association (ERSA), 2002)
A series of empirical studies has identified that a pervasive shift in the industrial structure away from large corporations and towards small enterprises has taken place between the mid-1970s and early 1990s. This shift occurred in virtually every single leading industrial country. The questions are whether such a shift is desirable and whether the resulting industrial structure should be promoted or avoided? From an empirical perspective there is growing evidence on the relation between size class distributions and economic performance. However, the question whether this change of the size class structure of industries has influenced economic performance is still underresearched. This has to do with a persistent lack in knowledge concerning questions like who enters and exits, what determines this mobility and what are its effects, in particular on economic performance. Empirical findings so far regarding to the economic effects of turbulence show mixed results. As entry and exit rates are rising, knowledge about the economic effects of turbulence is important for national and regional policymakers, as well as scientists. The purpose of this study is to assess the effect of entry and exit of firms on productivity in a regional approach. A model for total factor productivity is estimated using data of 40 Dutch regions for the years 1988 through 1996. The regions can be desaggregated into two separate sectors: manufacturing and services. For the regions and sectors information about firm dynamics (number of entries, exits and existing firms) and economic indicators is available for the years 1988-1996. The findings indicate some positive effects of turbulence on total factor productivity of regions and thereby on productivity and growth at macro-level. In the service sector it was found that turbulence has an upward impact on the TFP growth in a region. It was also found that the effect of turbulence does not occur immediately. The estimates indicate that the effect is measurable after one year but that the effect is more pronounced after two years. No TFP effect of turbulence was found for manufacturing. However, entry and exit processes in the services sector may also affect performance in manufacturing as the sectors are interrelated in many regions.
Keywords: 330